The Effect of the Addition Steel Slag and Bamboo Leaf Ash on the CBR Unsoaked Value in Subgrade Stabilization - Kusuma, Rama Indera; Mina, Enden; Fathonah, Woelandari; Ramadhan, Thanara; Abdurohim, Abdurohim (JURUSAN TEKNIK SIPIL, 2023)
This research was conducted to determine the physical and mechanical properties of origin and mixed soil with added steel slag (SS) and bamboo leaf ash (BLA) and to determine soil classification based on the Unified Soil Classification System (USCS) guidelines. This study used a mixture of steel slag and bamboo leaf ash with variations (0% SS ; 0% BLA), (20% SS; 10% BLA), (40% SS; 10% BLA), (60% SS, 10 % BLA), (100% SS; 10% BLA) with a curing time of 0 and 7 days. The mechanical properties test in this study was the unsoaked CBR test. In the USCS soil type classification system at the road location, it is included in the OH group (organic clay with high plasticity) with a plasticity index value of 22.86%, a liquid limit above 50%, which is equal to 64.5% and a DCP (Dynamic Cone Penetrometer) was obtained by 3.01%. The results showed that mixing native soil with added materials increased the CBR value. The optimum soil CBR value is found in the percentage of added material, 100% steel slag, and 10% bamboo leaf ash during seven days of curing with an unsoaked CBR value of 24.95%.